Experimental studies on gasification performance of sawdust and sawdust pellet in a downdraft biomass gasifier - Fatin Zafirah, Mansur; Che Ku Mohammad Faizal, Che Ku Yahya; Noor Asma Fazli, Abdul Samad; Atnaw, Samson Mekbib; Shaharin, Sulaiman (Universiti Malaysia Pahang, 2019)
In this work, a comparative analysis of the gasification process of sawdust (SW) and sawdust pellet (SWP) utilizing a downdraft gasifier was performed. The gasification was conducted in a research-scale fixed-bed gasifier applying air as an oxidizing agent. The comparison between the raw (sawdust, SW) and treated biomass (sawdust pellet, SWP) was investigated for the syngas composition and gasification performance at the fixed condition of gasification temperature at 750 °C and equivalence ratio of 0.25. The gasification performance was tabulated in the form of heating value of the syngas (HHVsyngas), gasification efficiency (ηGE) and carbon conversion efficiency (ηCCE). It was found out that SWP produced the highest H2 and the lowest CO2. Furthermore, SWP also present the better gasification performance than SW. SWP achieved the high HHVsyngas, ηGE, and ηCCE at 4.2152 MJ/Nm3, 24% and 37%, respectively